The Relationship between the Method of Cardioplegia and Vascular Endothelial Cell Derived Soluble Adhesion Molecules in Myocardial Ischemia-Reperfusion Injury - (:unkn) unknown (My University, 2003)
The relative role of different adhesion molecules in the ischemia-reperfusion injury after cardioplegic arrest in the clinical setting is unknown, because of protective effects of cardioplegia and hypothermia. The aim of this study is to determine the relationship between the method of the cardioplegia and endothelial derived soluble adhesion molecules; soluble vascular adhesion molecule-1 (sVCAM-1) and soluble intercellular adhesion molecule-1 (sICAM-1) in myocardial ischemia-reperfusion injury. Fourteen male patients who underwent aortocoronary bypass surgery with cardiopulmonary bypass were included in this study. They were randomised to be given blood or crystalloid cardioplegia for myocardial protection. Group I (n = 7) received blood cardioplegia and group II (n = 7) received crystalloid cardioplegia. The cross-clamp times were not significantly different between the two groups, 49.4±4.6 min for group I and 54.8±12.5 min for group II. Mean age of patients was 58±2.1 years for group I and 54±2.6 years for group II. Blood samples were taken from both the aorta and coronary sinuses of all patients before cross-clamp, after cross-clamping and at 30th min of reperfusion. Plasma were obtained from blood samples and then stored at −70°C. sVCAM-1 and sICAM-1 levels were measured by ELISA in the samples. There were no significant differences in the levels of sICAM-1 and sVCAM-1 at the beginning of reperfusion and at 30th min of reperfusion in coronary sinus of group I patients. But, increased sICAM-1 and sVCAM-1 levels were observed at 30th min of reperfusion in blood taken from coronary sinuses of group II patients compared with beginning of reperfusion (respectively p = 0.01, p = 0.03). In conclusion, these results have shown that ischemia-reperfusion injury is more likely to occur in patients protected by crystalloid cardioplegia, and suggest that blood cardioplegia may be preferred especially in borderline myocardial functioned patients. © 2003, SAGE Publications. All rights reserved.
Keywords: cardioplegia; ischemia-reperfusion injury; soluble adhesion molecules